Mental Health Care for Service Members and Their Families Across the Globe. (21st March 2019) - McGraw, Kate; Adler, Jamie; Andersen, Søren B; Bailey, Suzanne; Bennett, Clare; Blasko, Kelly; Blatt, Andrew D; Greenberg, Neil; Hodson, Stephanie; Pittman, Demietrice; Ruscio, Aimee C; Stoltenberg, Christian D G; et al.
Abstract: The U.S. Defense Department partnered with the International Initiative for Mental Health Leadership on effective leadership and operational practices for delivery of mental health (MH) as well as addiction services throughout the world for Service Members (SM) and beneficiaries. A Military Issues Work Group (MIWG) was established in 2011 to focus on challenges experienced by military SM and beneficiaries among countries. The MIWG found common concerns related to MH care delivery to rural and remote beneficiaries. Gaps in access to care were identified and prioritized to explore. This led to better collaboration and understanding of telemental health (TMH) practices and technology applications (apps) which increase access to care for rural and remote SMs and beneficiaries. An assessment of the number of SMs and dependents distant from MH care services in the USA was conducted, as well as an environmental scan for psychological health-focused mobile apps and TMH services geared toward SM, veterans, and beneficiaries. The MIWG is developing a compendium of existing military TMH programs and apps that address MH concerns and extant literature on use of technology to extend global access to care for military members and their families across the world.